PRISMA-Based Study on Integrating Islamic Principles into Legal Systems: Human Rights in Egypt and Indonesia - AN, Andri Nirwana; Elbanna, Mariam; Ismail, Faisal Husen; Daud, Zainora; Mohd Salleh, Norsaleha; bin Kirin, Arwansyah; Marisa, Siti Nurkhafifah; Husein, Muhammad Zakir (International Journal of Law and Society, 2024)
This study explores the application of Qur'anic human rights principles in Egypt and Indonesia, focusing on how Islamic teachings are integrated into modern legal systems amidst different cultural, political, and historical contexts. The study investigates the balance between universal human rights standards and Islamic jurisprudence, identifying variations in the interpretation and application of these principles in both countries. The PRISMA framework was used as the basis for the method, ensuring a systematic and transparent approach to reviewing legal texts, academic literature, and case studies. The technique began by identifying sources relevant to applying human rights law in the context of Islamic teachings in Egypt and Indonesia. A focused search was conducted using Web of Science and Scopus databases, targeting articles published between 2014 and 2024. Inclusion criteria ensured that the study analyzed recent and high-quality research on the intersection of Qur'anic principles and international human rights standards. The study shows that Egypt faces challenges in implementing Qur'anic teachings due to conservative interpretations that limit gender equality, freedom of expression, and freedom of religion. In contrast, Indonesia is more flexible by balancing Islamic principles with modern democratic values. This allows for a broader interpretation of Qur'anic principles, especially gender equality and religious freedom. The role of ijtihad in Indonesia is crucial in adapting Islamic law to contemporary human rights standards. This study highlights the complexity of aligning Islamic teachings with global human rights norms. It emphasizes the importance of revisiting traditional interpretations of the Qur'an to better align them with contemporary values ​​of justice, equality, and human dignity, as well as ensuring respect for the human rights of all citizens.